MATLAB for Control System Engineers (2nd Edition) - Dukkipati, Rao V (New Academic Science, 2014)
This book is designed as an introductory undergraduate or graduate course for science and engineering students of all disciplines. Control systems engineering is a multidisciplinary subject and presents a control engineering methodology based on mathematical fundamentals and stresses physical system modeling. The classical methods of control systems engineering are covered here using MATLAB software: matrix analysis, Laplace transforms and transfer functions, root locus analysis and design, frequency response methods of analysis including Bode, Nyquist, and Nichols, second order systems approximations, phase and gain margin and bandwidth, and state space variable method. Presentations are limited to linear, time-invariant continuous systems. The numerous worked examples (over 400 problems and solutions) are intended to provide the reader with an awareness of the general applicability of control theory using MATLAB. An extensive bibliography to guide the students to further sources of information on control systems engineering using MATLAB is provided at the end of the book.